2012
DOI: 10.1039/c2an16148f
|View full text |Cite
|
Sign up to set email alerts
|

A dual sensor of fluorescent and colorimetric for the rapid detection of lead

Abstract: This study demonstrated a simple and reliable method to rapidly detect Pb(2+) in aqueous solution, exploiting gold nanoparticles as a lead ion probe; the results indicated that the dual channels sensor showed high selectivity and sensitivity for Pb(2+) as low as ppm levels in aqueous environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…To our knowledge, the glycosidic bond cleavage of native carbohydrates has been reported to initiate from the reducing end [9][10][11][12][13][14][15][16][17][18][19]. However, in this study, the glycosidic bond cleavage of PMP labeled oligosaccharides was found to initiate from the nonreducing end, which was demonstrated by the MS/MS spectra of PMP labeled ␣(1 → 4)-linked maltotriose and maltotetrose (Fig.…”
Section: Fragmentation Of Pmp Labeled Carbohydratecontrasting
confidence: 78%
See 1 more Smart Citation
“…To our knowledge, the glycosidic bond cleavage of native carbohydrates has been reported to initiate from the reducing end [9][10][11][12][13][14][15][16][17][18][19]. However, in this study, the glycosidic bond cleavage of PMP labeled oligosaccharides was found to initiate from the nonreducing end, which was demonstrated by the MS/MS spectra of PMP labeled ␣(1 → 4)-linked maltotriose and maltotetrose (Fig.…”
Section: Fragmentation Of Pmp Labeled Carbohydratecontrasting
confidence: 78%
“…The conventional analysis for carbohydrates involves a combination of techniques such as NMR, GC/MS, and monosaccharide composition analysis [7,8]. With the development of matrix-assisted laser desorption/ionization (MALDI) and electrospray ionization (ESI) mass spectrometry (MS), mass spectrometry-based analytical method has been proved to be one of the most powerful and versatile techniques for the structural analysis of carbohydrates because of its low sample consumption, high sensitivity, and short acquisition times [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 represents the comparison of the limits of detection of various methods that have been developed involving nanomaterials as the nanoprobes [54][55][56][57][58][59][60][61]. The proposed method using SiO 2 @Au NCs shows high selectivity and sensitivity for the necked eye detection upto 50 nM…”
Section: Comparison and Selectivitymentioning
confidence: 98%
“…reported a bromide capped gold nanoparticles for sensing lead. 74 In this case, Pb 2+ reacts with bromide ions to form PbBr 2 on the surface of the gold nanoparticles that exhibits luminescence by absorbing in the UV region (300 nm) with visible emission (600 nm). With an increase in Pb 2+ concentration the color of the particles changes from red to light blue and even become colorless which can be visualized with naked eyes.…”
Section: Nanoparticlesmentioning
confidence: 99%